Harper's illustrated biochemistry - Rodwell, Victor W.; Bender, David A.; Botham, Kathleen M.; Kennelly, Peter J.; Weil, P. Anthony (New York : McGraw-Hill Education, 2023)
"The thirty-first edition of Harper's Illustrated Biochemistry continues to emphasize the link between biochemistry and the understanding of disease states, disease pathology, and the practice of medicine. Featuring a full-color presentation and numerous medically relevant examples, Harper's presents a clear, succinct review of the fundamentals of biochemistry that every student must understand in order to succeed in medical school"--
Section I: Structures & Functions of Proteins & Enzymes -- Chapter 1: Biochemistry & Medicine -- Chapter 2: Water & pH -- Chapter 3: Amino Acids & Peptides -- Chapter 4: Proteins: Determination of Primary Structure -- Chapter 5: Proteins: Higher Orders of Structure -- Section II: Enzymes: Kinetics, Mechanism, Regulation, & Role of Transition Metals -- Chapter 6: Proteins: Myoglobin & Hemoglobin -- Chapter 7: Enzymes: Mechanism of Action -- Chapter 8: Enzymes: Kinetics -- Chapter 9: Enzymes: Regulation of Activities -- Chapter 10: The Biochemical Roles of Transition Metals -- Section III: Bioenergetics -- Chapter 11: Bioenergetics: The Role of ATP -- Chapter 12: Biologic Oxidation -- Chapter 13: The Respiratory Chain & Oxidative Phosphorylation -- Section IV: Metabolism of Carbohydrates -- Chapter 14: Overview of Metabolism & the Provision of Metabolic Fuels -- Chapter 15: Carbohydrates of Physiological Significance -- Chapter 16: The Citric Acid Cycle: The Central Pathway of Carbohydrate, Lipid, & Amino Acid Metabolism -- Chapter 17: Glycolysis & the Oxidation of Pyruvate -- Chapter 18: Metabolism of Glycogen -- Chapter 19: Gluconeogenesis & the Control of Blood Glucose -- Chapter 20: The Pentose Phosphate Pathway & Other Pathways of Hexose Metabolism -- Section V: Metabolism of Lipids -- Chapter 21: Lipids of Physiologic Significance -- Chapter 22: Oxidation of Fatty Acids: Ketogenesis -- Chapter 23: Biosynthesis of Fatty Acids & Eicosanoids -- Chapter 24: Metabolism of Acylglycerols & Sphingolipids -- Chapter 25: Lipid Transport & Storage -- Chapter 26: Cholesterol Synthesis, Transport, & Excretion -- Section VI: Metabolism of Proteins & Amino Acids -- Chapter 27: Biosynthesis of the Nutritionally Nonessential Amino Acids -- Chapter 28: Catabolism of Proteins & of Amino Acid Nitrogen -- Chapter 29: Catabolism of the Carbon Skeletons of Amino Acids -- Chapter 30: Conversion of Amino Acids to Specialized Products -- Chapter 31: Porphyrins & Bile Pigments -- Section VII: Structure, Function, & Replication of Informational Macromolecules -- Chapter 32: Nucleotides -- Chapter 33: Metabolism of Purine & Pyrimidine Nucleotides -- Chapter 34: Nucleic Acid Structure & Function -- Chapter 35: DNA Organization, Replication, & Repair -- Chapter 36: RNA Synthesis, Processing, & Modification -- Chapter 37: Protein Synthesis & the Genetic Code -- Chapter 38: Regulation of Gene Expression -- Chapter 39: Molecular Genetics, Recombinant DNA, & Genomic Technology -- Section VIII: Biochemistry of Extracellular & Intracellular Communication -- Chapter 40: Membranes: Structure & Function -- Chapter 41: The Diversity of the Endocrine System -- Chapter 42: Hormone Action & Signal Transduction -- Section IX: Special Topics (A) -- Chapter 43: Nutrition, Digestion, & Absorption -- Chapter 44: Micronutrients: Vitamins & Minerals -- Chapter 45: Free Radicals & Antioxidant Nutrients -- Chapter 46: Glycoproteins -- Chapter 47: Metabolism of Xenobiotics -- Chapter 48: Clinical Biochemistry -- Section X: Special Topics (B) -- Chapter 49: Intracellular Traffic & Sorting of Proteins -- Chapter 50: The Extracellular Matrix -- Chapter 51: Muscle & the Cytoskeleton -- Chapter 52: Plasma Proteins & Immunoglobulins -- Chapter 53: Red Blood Cells -- Chapter 54: White Blood Cells -- Section XI: Special Topics (C) -- Chapter 55: Hemostasis & Thrombosis -- Chapter 56: Cancer: An Overview -- Chapter 57: The Biochemistry of Aging -- Chapter 58: Biochemical Case Histories -- The Answer Bank
Includes bibliographical references and index
Keywords: Biochemistry; Clinical biochemistry